1)Solve homogeneous equation "y^{(4)}-2y'''+2y''=0".
Its characteristic equation is "\\lambda^4-2\\lambda^3+2\\lambda^2=0", solutions of which are "\\lambda_1=\\lambda_2=0, \\lambda_3=1+i, \\lambda_4=1-i".
So general solution of this equation is "y=Ax+B+e^x(C\\cos x+D\\sin x)"
2)Particular soltuion of "y^{(4)}-2y'''+2y''=3e^{-x}+2xe^{-x}+e^{-x}\\sin x"
Since "-1" and "-1+i" are not roots of the characteristic equation, pariclular solution of "y^{(4)}-2y'''+2y''=3e^{-x}+2xe^{-x}+e^{-x}\\sin x" is "y=(U+Vx)e^{-x}+e^{-x}(W\\cos x+T\\sin x)".
Calculate derivative of "z=(\\alpha+\\beta x)e^{-x}+e^{-x}(\\gamma\\cos x+\\delta\\sin x)" :
"z'=\\beta e^{-x}-(\\alpha+\\beta x)e^{-x}+e^{-x}(-\\gamma\\sin x+\\delta\\cos x)-"
"-e^{-x}(\\gamma\\cos x+\\delta\\sin x)="
"=(-\\beta x+\\beta-\\alpha)e^{-x}+e^{-x}((\\delta-\\gamma)\\cos x+(-\\gamma-\\delta)\\sin x)"
Then "y'=(-Vx+V-U)e^{-x}+"
"+e^{-x}((T-W)\\cos x+(-W-T)\\sin x)"
"y''=(Vx-2V+U)e^{-x}+e^{-x}(-2T\\cos x+2W\\sin x)"
"y'''=(-Vx+3V-U)e^{-x}+"
"+e^{-x}((2W+2T)\\cos x+(2T-2W)\\sin x)"
"y^{(4)}=(Vx-4V+U)e^{-x}+e^{-x}(-4W\\cos x-4T\\sin x)"
So "y^{(4)}-2y'''+2y''=(5Vx-14V+5U)e^{-x}+"
"+e^{-x}((-8W-8T)\\cos x+(8W-8T)\\sin x)" and we obtain
"\\begin{cases}\n-14V+5U=3\\\\\n5V=2\\\\\n-8W-8T=0\\\\\n8W-8T=1\n\\end{cases}"
That is "V=\\frac{2}{5}, U=\\frac{43}{25}, T=-\\frac{1}{16}, W=\\frac{1}{16}"
3)General solution of "y^{(4)}-2y'''+2y''=3e^{-x}+2xe^{-x}+e^{-x}\\sin x" is "y=Ax+B+e^x(C\\cos x+D\\sin x)+"
"+\\frac{1}{25}(43+10x)e^{-x}+\\frac{1}{16}e^{-x}(\\cos x-\\sin x)"
Answer:
"Ax+B+e^x(C\\cos x+D\\sin x)+"
"+\\frac{1}{25}(43+10x)e^{-x}+\\frac{1}{16}e^{-x}(\\cos x-\\sin x)"
Comments
Leave a comment